The influence of artificial aging on tensile properties of Al 6061-T4 - Freddy Saputra Romamti-Ezer Taebenu; Heryoga Winarbawa; Rines Rines; Budi Setyahandana; I Made Wicaksana Ekaputra (International Journal of Applied Sciences and Smart Technologies, 2022)
This paper presents an explanation related to experimental testing in the form of the tensile properties of Al 6061. Al 6061 was heat treated by the precipitation hardening method. The precipitation hardening consisted of T4 and T6 treatment. Al 6061 samples were heat-treated at a temperature of 430°C for 2 hours, then cooled slowly at room temperature. The T4 was conducted at a temperature of 530°C for 2 hours, followed by rapid cooling in a water medium and natural ageing at a temperature of 70°C for six days. Temperature T6 is the final process of applying precipitation hardening treatment to Al 6061. Temperature T6 is carried out at 530°C for 2 hours, then cooled rapidly in a water medium and continued with artificial ageing at 190°C with a variation of ageing time for 3 hours, 5 hours, and 7 hours. The effect of the applied treatment was observed to increase the maximum strength value of the tensile test of Al 6061.